2011
DOI: 10.1177/0885066611403110
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotics for the Treatment of ICU Delirium

Abstract: Delirium is commonly described in critically ill patients as 1 factor contributing to increased length of intensive care unit and hospital stay, secondary complications, and increased mortality. Initial screening tools for delirium in hospitalized patients are generally easy to use; however, many centers have struggled with implementing these tools in a consistent and systematic manner. Haloperidol has traditionally been prescribed as the primary agent of choice for the treatment of delirium in critically ill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Data regarding treatment interventions for HD are scarce. Although several studies have examined the use of antipsychotics for the management of delirium symptomatology [ 64 , 65 ], research on HD symptom management is limited. In a recent report it was found that symptoms of hypoactive delirious patients responded better than symptoms of hyperactive patients to the atypical antipsychotic aripiprazole [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding treatment interventions for HD are scarce. Although several studies have examined the use of antipsychotics for the management of delirium symptomatology [ 64 , 65 ], research on HD symptom management is limited. In a recent report it was found that symptoms of hypoactive delirious patients responded better than symptoms of hyperactive patients to the atypical antipsychotic aripiprazole [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…First‐generation antipsychotics primarily block postsynaptic D 2 receptors, whereas atypical antipsychotics also antagonize 5‐HT 2 receptors. Variable receptor affinity for α‐adrenergic, H 1 , and M 1 receptors by atypical antipsychotics also results in differences in adverse effects between these agents …”
Section: Use Of Antipsychotics In Patients With Ardsmentioning
confidence: 99%
“…Studies regarding use of psychotropic medicine in delirium treatment are scarce and only one reported beneficial effect of quetiapine. When compared to other antipsychotics, quetiapine has shortened the duration of delirium and reduced agitation (Gilchrist et al 2012). Antipsychotics are regularly used to relieve delirium, which can last for several weeks.…”
Section: Psychiatric Aspects Of the Post-transplant Periodmentioning
confidence: 99%